Complete genome of Nitrosospira briensis C-128, an ammonia-oxidizing bacterium from agricultural soil. Issue 1 (December 2016) - Rice, Marlen; Norton, Jeanette; Valois, Frederica; Bollmann, Annette; Bottomley, Peter; Klotz, Martin; Laanbroek, Hendrikus; Suwa, Yuichi; Stein, Lisa; Sayavedra-Soto, Luis; Woyke, Tanja; Shapiro, Nicole; et al.
Abstract Nitrosospira briensis C-128 is an ammonia-oxidizing bacterium isolated from an acid agricultural soil.N. briensis C-128 was sequenced with PacBio RS technologies at the DOE-Joint Genome Institute through their Community Science Program (2010). The high-quality finished genome contains one chromosome of 3.21 Mb and no plasmids. We identified 3073 gene models, 3018 of which are protein coding. The two-way average nucleotide identity between the chromosomes ofNitrosospira multiformis ATCC 25196 andNitrosospira briensis C-128 was found to be 77.2 %. Multiple copies of modules encoding chemolithotrophic metabolism were identified in their genomic context. The gene inventory supports chemolithotrophic metabolism with implications for function in soil environments.